Lando - L'Amour, Louis (Thorndike Press, 1962)
Sackett got to Texas with a well-oiled dogleg, a racing mule that didn't look worth its salt and a damn good idea of the whereabouts of buried gold across the border in Mexico. In Mexico he had bad luck. His party had to run for it, and when Lando stood rear guard they pulled out and left him. Six years in a Mexican prison put muscles in his arms, fire in his heart and pure recklessness in his head. When he caught up with the men who betrayed him, it made no difference that he didn't have a gun.
Keywords: Large Print